Mutações constitucionais promovidas pelo supremo tribunal federal: Uma análise representativa de julgados de 2016 a 2018 - REIS, Natália de Jesus Silva (2020)
Constitutional changes play a fundamental role in the permanence and continuity of the constituent work and greatly influence at the identification of the rule of law with the ideals of a democratic regime. This happens due to its conciliatory task between the grandeurs of stability and dynamics of the constitutional order. Constitutional changes accompany the transformations of reality and society to make the fundamental order compatible with the new generation that intends to legally conform, allowing constitutional rules to be effectively implemented. Precisely because they are mechanisms limited by the provisions of the original constituent power, the constituted powers and their institutions must opt for restricted actions when modifying the Constitution. However, such an objective is not always satisfied and although certain conflicts and tensions between the Powers are natural in the composition of a constitutional democracy the problem lies in the overuse of channels for constitutional change, especially informal ones. The informal changes known as constitutional mutations modify the meaning, sense and scope of the constitutional norm in a way that its linguistic statement remains unchanged. This silent character of constitutional mutations becomes worrisome when the rules of the democratic game are weakened to such an extent that it leads to the non-observance of its limits and the diminishing of the mechanims of control, which opens the way to the subversion of the meaning of constitutional norms. Through their misuse, mutations assume the status of unconstitutional and undermine the text and spirit of the Constitution, increasing any crisis that may have given rise to it. Therefore, the present research aims to analyze the relevance of the constitutional mutations promoted by the Supreme Federal Court, considering the accentuated historic of amendments to the 1988 Constitution and the troubled political-legal scenario Brazil went throught in the period of 2016 to 2018. The methodological approach followed the lines drawn by the method of historical-dialectical materialism, taking into account the analysis of constitutional mutations as an instrument inspired by the transformations of the sociopolitical, economic and cultural basis of reality; with the complementary assistance of the comparative method, which allowed the reconstruction of the historical-conceptual trajectory of the mutations within the German public law and the comparison with the Brazilian context in which it was incorporated. Finally, the analysis of the decisions of the Supreme Federal Court perceived by the Court itself as "constitutional changes" in the interstitium from 2016 to 2018 allowed the examination of the arguments used by its judges towards the institute, the procedural instruments that most often introduced these informal changes and the teoric branch that prevails on the subject.